Rice Seed Germination Underwater: Morpho-Physiological Responses and the Bases of Differential Expression of Alcoholic Fermentation Enzymes - Miro, Berta; Longkumer, Toshisangba; Entila, Frederickson D.; Kohli, Ajay; Ismail, Abdelbagi M. (Frontiers in Plant Science, 2017)
The water-, energy- and labor-intensive system of transplanted puddled rice (Oryza sativa) is steadily being replaced by direct seeding due to the progressive scarcity of these resources. However, the alternate dry direct seeding leads to competition with weeds and poor establishment when soils are flooded. Direct seeded rice capable of anaerobic germination (germination in flooded soil, AG) is ideal, which under rainfed ecosystems would also combat waterlogging during germination. AG tolerance is associated with faster germination and faster elongation of coleoptiles, with the activities of alcoholic fermentation enzymes replacing aerobic respiration as a source of energy. To better understand the variability in the morpho-physiological responses and in the nature of the alcoholic fermentation enzymes during AG, 21 rice genotypes were studied. The genotypes Khao Hlan On (KHO) and IR42 were used as the tolerant and susceptible checks respectively. KHO exhibited faster germination, with 82.5% of the coleoptiles emerging out of 10 cm of water within 8 days, whereas IR42 exhibited 20% germination and limited coleoptile growth. Among the test genotypes, four performed well, including two that are drought tolerant. Increased content and activity of the alcoholic fermentation enzymes, alcohol dehydrogenase (ADH1) and acetaldehyde dehydrogenase (ALDH2a and ALDH2b), was noted in KHO under anaerobic than under aerobic conditions and also in comparison with IR42 under AG. Gene transcripts for these enzymes were also more in KHO undergoing AG. However, no major differences existed between KHO and IR42 in the critical cis-acting regulatory elements, such as the auxin, light, and sugar response elements, in the promoters of ADH1, ALDH2a and ALDH2b genes. Post-transcriptional and post-translational regulatory mechanisms were implicated for the increased transcript and protein content/activity of the enzymes in KHO by observing four different transcripts of ALDH2a and a unique non-glycosylated form of ADH1 under AG. IR42 lacked the non-glycosylated ADH1 and contained only a truncated form of ALDH2a, which lacked the active site. Additionally, KHO exhibited increased activity and more isoforms for reactive oxygen species (ROS) detoxifying enzymes under AG compared to IR42. These results highlight the need for a deeper functional understanding of the critical enzymes involved in AG